Market menagerie : health and development in late industrial states - Srinivas, Smita (Stanford Economics and Finance, an imprint of Stanford University Press, 2012)
Srinivas examines technological advance and market regulation in the health industries of nations such as India, Brazil, South Africa, Nigeria, and China. Pharmaceutical and life science industries can reinforce economic development and industry growth, but not necessarily positive health outcomes. Yet well-crafted industrial and health policies can strengthen each other and reconcile economic and social goals. This book advocates moving beyond traditional market failure to bring together three uncommonly paired themes: the growth of industrial capabilities, the politics of health access, and the geography of production and redistribution.